Conservation and Production of Ipecac (Cephaelis ipecacuanha Rich.) Plants from Long Term Shoot Cultures - Chaudhuri, Rituparna Kundu; Jha, Timir Baran (Plant Tissue Culture and Biotechnology, 2009)
In vitro germplasms of ipecac (Cephaelis ipecacuanha Rich.), an important medicinal plant, maintained through reduced growth conditions for more than 12-years, were used as source material for micropropagation. MS with different combinations of Kn (2 mg/l), BAP (2 mg/l), 2iP (2-3 mg/l), NAA (0.2 mg/l) and adenine (40-100 mg/l) as additive was used to induce fresh multiplication of shoots from the nodal meristems and direct shoot bud initiation on the internodal segments. Complete plant regeneration has been achieved from such long term cultures. Regenerated plants maintained their phenotypic and chromosomal stability. Eighty per cent hardened plants, survived in the field condition, are growing well and 25% of them produced flowers within one year. Long term preservation through reduced growth conditions and successful regeneration of morphologically stable plants with stable chromosome numbers (2n = 22) from such long term cultures of ipecae plants. Key words: Long term culture, Ipecac, micropropagation, flowering D.O.I. 10.3329/ptcb.v18i2.3646 Plant Tissue Cult. & Biotech. 18(2): 157-164, 2008 (December)